Student Stress Levels in Academic Learning During the Covid-19 Pandemic - Asri Azani; Ghazal Elram; Robinson Eric (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
This study aims to determine the level of stress of junior high school students in learning during the Covid-19 pandemic in Nagari Pangian, Lintau Buo District. The type of research used is quantitative descriptive research. The confession of reliability is 0.96,4, with a total of 60 items covering four psychological, physiological, cognitive, and behavioral factors. There are four choices of stress levels in selecting categories in collecting data: strongly agree, agree, degrees during, and strongly disagree. The level of the stress of junior high school students in academic learning during the Covid-19 pandemic was in the high category, where 30 subjects (22.7%) were at moderate stress levels, 63 subjects (47.7%) were at high-stress levels, and 39 subjects (29.5%) were at very high-stress levels.